A revision of Hierochloe sect. Monoecia (Anthoxanthinae, Pooideae, Poaceae) - Lema-Suárez, Irene; Sahuquillo, Elvira; Pimentel, Manuel (Phytotaxa, 2021)
We propose a new taxonomic arrangement for the South American species of Hierochloe sect. Monoecia, based on a recently published study combining morphological, molecular and cytological data. Only four out of the eight commonly accepted species of this section (H. pusilla, H. juncifolia, H. quebrada and H. redolens pro parte) are recognised using both phylogenetic (apomorphic) and phenetic species concepts. The four remaining species (H. altissima, H. gunckelii, H. spicata and H. utriculata) are reduced to varieties of the widespread H. redolens due to weak molecular, macro- and micromorphological differentiation. These varieties are presented here as new taxonomical combinations: H. redolens var. gunckelii, H. redolens var. spicata, H. redolens var. utriculata and H. redolens var. altissima. Lectotypes are designated for the names H. pusilla, H. juncifolia, H. redolens var. utriculata, and H. redolens var. altissima.